SOSIALISASI SMART LIGHT BERBASIS MICROKONTROLLER - Agustina, Ulfa Wulan; Bahtiar, Yuyun; Ma'arif, Iin Baroroh; Afidah, Nurul; Nisak Nur, Luluk Choirun (ABIDUMASY, 2024)
The Microcontroller-based Smart Light Socialization Program for Village Apparatus aims to introduce smart technology that can improve the efficiency of electrical energy use in rural areas. This Smart Light system uses a microcontroller integrated with light sensors and motion sensors to automatically turn lights on and off, according to environmental conditions. The approaches or methods used in community service activities include Participatory Action Research (PAR). In this case, students conduct direct research in Kepuhrejo Village to implement the knowledge they have gained in the village community. This PAR is transformative and empowers the community. In addition, this community service activity also uses the Service Learning (SL) method, where in its implementation it directly involves the participation of participants, namely the target audience in this activity so that the Microcontroller-based Smart Light Introduction work program is created. This program has succeeded in increasing village apparatus awareness of Smart Light technology and its benefits in energy efficiency and environmental safety.